2014
DOI: 10.1002/art.38904
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Rheumatoid Arthritis–Associated Interstitial Lung Disease

Abstract: Objective Interstitial lung disease (ILD) is a relatively common extraarticular manifestation of rheumatoid arthritis (RA) that contributes significantly to disease burden and excess mortality. The purpose of this study was to identify peripheral blood markers of RA-associated ILD that can facilitate earlier diagnosis and provide insight regarding the pathogenesis of this potentially devastating disease complication. Methods Patients with RA who were enrolled in a well-characterized Chinese identification co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 36 publications
4
115
1
5
Order By: Relevance
“…Baseline demographics and smoking history were obtained from the medical records. We have previously reported subject characteristics of the BRASS and ACR cohorts (18,25). More details including timing of the serum samples, autoantibodies, and PFTs are found in the online supplement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline demographics and smoking history were obtained from the medical records. We have previously reported subject characteristics of the BRASS and ACR cohorts (18,25). More details including timing of the serum samples, autoantibodies, and PFTs are found in the online supplement.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, risk factors for RA-ILD and most idiopathic interstitial pneumonias include older age, male sex, and smoking (16)(17)(18)(19)(20)(21). Moreover, our group has recently shown that peripheral blood levels of matrix metalloproteinase-7 (MMP7), a biomarker associated with survival in IPF (22)(23)(24), are significantly elevated in patients with RA with both clinically established and subclinical ILD (25). Based on these findings we hypothesize that validated IPF biomarkers associated with clinical outcomes, such as MMP7, pulmonary and activation-regulated chemokine (PARC)/CCchemokine ligand-18 (26,27), and surfactant protein D (SP-D) (28)(29)(30)(31), could identify RA-ILD (6).…”
mentioning
confidence: 99%
“…Oka et al [5] suggested HLA-DQB1*03:01 as risk alleles of bronchiectasis or emphysema in RA. For biomarkers, matrix metalloproteinases-7, CXCL10, pulmonary and activation-regulated chemokine, and surfactant protein D were increased in RA with ILD patients compared to RA without ILD [15,16]. Tumor markers such as CA15-3, CA125, and CA19-9 were specifically increased in the sera of RA-ILD patients [3].…”
Section: Lung Disease In Rheumatoid Arthritismentioning
confidence: 93%
“…Biomarkers were first studied in IPF, where higher levels of MMP-7 and SP-D are associated with reduced survival 31,32 . In RA ILD, a combinatorial signature including MMP-7 and IP-10 (a chemokine related to Th1 lymphocyte trafficking) significantly increased the detection of the disease, while MMP-7 and SP-D have also been shown to enhance our ability to risk-stratify clinically evident and subclinical disease 33,34 . However, the role of these or other biomarkers in clinical practice needs to be clarified.…”
Section: Noninvasive Strategymentioning
confidence: 99%